Allocation under Dictatorship: Research in Stalin's Archives - Gregory, Paul; Harrison, Mark (Journal of Economic Literature, 2005)
We survey recent research on the Soviet economy in the state, party, and military archives of the Stalin era. The archives have provided rich new evidence on the economic arrangements of a command system under a powerful dictator including Stalin's role in the making of the economic system and economic policy, Stalin's accumulation objectives and the constraints that limited his power to achieve them, the limits to administrative allocation, the information flows and incentives that governed the behavior of economic managers, the scope and significance of corruption and market-oriented behavior, and the prospects for economic reform.